Anticoagulation use in perioperative atrial fibrillation after noncardiac surgery: a systematic review and meta-analysis - Michael Ke Wang; Rachel Heo; Pascal B. Meyre; Steffen Blum; Louis Park; Lauren Birchenough; Kiven Vuong; William F. McIntyre; Jeff S. Healey; Philip J. Devereaux; Michael McMullen; Marko Mrkobrada; et al. (Swiss Medical Weekly, 2023)
BACKGROUND: Perioperative atrial fibrillation is associated with an increased risk of stroke, myocardial infarction, and death after noncardiac surgery. Anticoagulation therapy is effective for stroke prevention in nonsurgical atrial fibrillation, but its efficacy and safety in perioperative atrial fibrillation are unknown.